Large Field, High Resolution Full-Field Optical Coherence Tomography: A Pre-Clinical Study of Human Breast Tissue and Cancer Assessment. (October 2014) - Assayag, Osnath; Antoine, Martine; Sigal-Zafrani, Brigitte; Riben, Michael; Harms, Fabrice; Burcheri, Adriano; Grieve, Kate; Dalimier, Eugénie; Le Conte de Poly, Bertrand; Boccara, Claude
We present a benchmark pilot study in which high-resolution Full-Field Optical Coherence Tomography (FF-OCT) was used to image human breast tissue and is evaluated to assess its ability to aid the pathologist's management of intra-operative diagnoses. FF-OCT imaging safety was investigated and agreement between FF-OCT and routinely prepared histopathological images was evaluated. The compact setup used for this study provides 1μm 3 resolution and 200μm imaging depth, and a 2.25 cm 2 specimen is scanned in about 7 minutes. 75 breast specimens were imaged from 22 patients (21 women, 1 man) with a mean age of 58 (range: 25–83). Pathologists blind diagnosed normal/benign or malignant tissue based on FF-OCT images alone, diagnosis from histopathology followed for comparison. The contrast in the FF-OCT images is generated by intrinsic tissue scattering properties, meaning that no tissue staining or preparation is required. Major architectural features and tissue structures of benign breast tissue, including adipocytes, fibrous stroma, lobules and ducts were characterized. Subsequently, features resulting from pathological modification were characterized and a diagnosis decision tree was developed. Using FF-OCT images, two breast pathologists were able to distinguish normal/benign tissue from lesional with a sensitivity of 94% and 90%, and specificity of 75% and 79% respectively.